The contribution of technopreneurship scientific learning and learning readiness towards the entrepreneurship learning outcomes in higher vocational education - Hendra Hidayat; Boy Yendra Tamin; Susi Herawati; Khairul Khairul; Eril Syahmaidi (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2019)
This research was motivated by the entrepreneurship learning outcomes in vocational education which is still poor. Technopreneurship scientific learning and learning readiness are assumed to be factors affecting entrepreneurship learning outcomes. The purpose of this study is to describe and test the contribution of technopreneurship scientific learning and readiness to learning of entrepreneurship learning outcomes. This research used the quantitative method with correlation descriptive. The population was all students who follow the general course of entrepreneurship in Higher Education for 1100 people. While the samples are 217 students who were selected by using proportional stratified random sampling. This research tool was a Likert scale and a valid and reliable reading comprehension test. Data were analyzed using descriptive statistics, simple regression and multiple regressions. The research findings show that there is a contribution of both technopreneurship scientific learning and learning readiness to entrepreneurship learning outcomes.